Effects of Leaf Storage and Distillation Time on the Quality of Eucalyptus (Eucalyptus grandis) Essential Oil - Setiawan Setiawan; Annisa Nadhilah; Rita P Ilhamsari (3BIO: Journal of Biological Science, Technology and Management, 2022)
Essential oils such as eucalyptus oil are widely used as antioxidants, antimicrobial, anti-inflammatory, fragrance, and other medical needs. This oil is extracted from eucalyptus terpenoid compounds, e.g., cineole. This study aims to evaluate the effect of the leaf storage time and distillation time (DT) on Eucalyptus grandis essential oil yield and quality. Three DT treatments (i.e., 2 h, 3 h, and 4 h) and storage time of eucalyptus leaf in warehouse (i.e., 2 h, 3 h, and 4 h) were applied on eucalyptus leaf samples. The quality of the eucalyptus essential oil was determined using cineole content, solubility in alcohol, and optical rotation. The essential oil yield ranges between 0.165-0.220%, with the maximum yield of 0.220% on 3 days of storage and 4-hour distillation time. The cineole content ranged between 10-30% and the highest at 3 h DT with a storage time of 2 days. The optical rotation on the tested specimen showed that the index of refraction produced in oil projections was positive. The samples in all treatments showed high solubility in alcohol. This study showed that storage time of 3 days and 3-hour distillation time resulted in the most optimal eucalyptus essential oil yield, and the excellent quality of oil produced has a high potential for health product applications.